Comprehensive analysis and experimental verification reveal the molecular characteristics of EGLN3 in pan-cancer and its relationship with the proliferation and apoptosis of lung cancer - Shi, Yuan-Xiang; Dai, Peng-Hui; Chen, Tao; Yan, Jian-Hua (Heliyon, 2024)
Egl-9 family hypoxia-inducible factor 3 (EGLN3) is involved in the regulation of tumor microenvironment and tumor progression. However, its biological function and clinical significance in various cancers remain unclear. RNA-seq, immunofluorescence, and single-cell sequencing were used to investigate the expression landscape of EGLN3 in pan-cancer. The TISCH2 and CancerSEA databases were used for single-cell function analysis of EGLN3 in tumors. TIMER2.0 database was used to explain the relationship between EGLN3 expression and immune cell infiltration. In addition, the LinkedOmics database was used to perform KEGG enrichment analysis of EGLN3 in pan-cancer. siRNA was used to silence gene expression. CCK8, transwell migration assay, flow cytometry analysis, RT-PCR, and western blotting were used to explore biological function of EGLN3. The results showed that EGLN3 was highly expressed in a variety of tumors, and was mainly localized to the cytosol. EGLN3 expression is associated with immunoinfiltration of a variety of immune cells, including macrophages in the tumor immune microenvironment and tumor-associated fibroblasts. Functional experiments revealed that EGLN3 knockdown could inhibit cell proliferation, migration, and promote cell apoptosis. In addition, we found that Bax expression was up-regulated and Bcl-2 expression was down-regulated in the si-EGLN3 group. Taken together, as a potential oncogene, EGLN3 is involved in the regulation of tumor malignant process, especially tumor cell apoptosis. We comprehensively investigated the expression pattern, single-cell function, immune infiltration level and regulated signaling pathway of EGLN3 in pan-cancer. We found that EGLN3 is an important hypoxia and immune-related gene that may serve as a potential target for tumor immunotherapy.